The Populus MYB transcription factor PSAR1 negatively regulates salt stress and is a repressor of ABA signaling - Qing Fang; Caiyun Zhang; Jingjie Liu; Zhi Zeng; Yanke Lu (Journal of Plant Interactions)
Plant transcription factors and their associations with ABA (abscisic acid) are critical for development and adaptation to environments. Here, we report that the Populus MYB transcription factor Salt stress – and ABA signaling-Repressor 1 (PSAR1) combines with ABA signaling to negatively regulate salt stress responses. A markedly diminished tolerance to salt stress was observed in the engineered Arabidopsis overexpressing PSAR1 (OeLAs) compared with Wt (wild-type) plants. OeLAs seed germination to ABA (1.0 μM) was less sensitive. Whereas by higher ABA (5.0 μM) treatment a delayed blooming was viewed in the OeLAs seedlings. And the endogenous ABA level steadily decreased. Furthermore, 486 DEGs (differentially expressed genes) were identified in OeLA1 by RNA-seq, including the genes encoding the Highly ABA-Induced protein phosphatases HAI1 and HAI2. A similar expression pattern of the genes was also confirmed by qRT-PCR. Overall, these results illuminate the Populus PSAR1 mediates environmental conditions, gene expression, and physiological ABA status.